Faktor – Faktor yang Mempengaruhi Kecemasan Orang Tua pada Anak Pra-operasi Di Ruang Bedah Anak - Dwi Novrianda, S.Kep, M.Kep; Hermalinda Hermalinda; Musymiratul Fauziah (NERS Jurnal Keperawatan)
Parental anxiety in the child's preoperative phase is influenced by various factors. This study aimed to determine the factors that affect parents' anxiety in preoperative children in the child's surgery room. Quantitative research with cross sectional study approach has been done in dr. M. Djamil Hospital Padang. The sampling technique used accidental sampling with 30 samples. This research took time from June 20 – July 30, 2016. Data were analyzed using independent sample t-test, with p <0.05. t-Test results showed the variables that influence anxiety of parents in pre operative children were parents’s education (p=0,006), parents’ knowledge (p=0,001), family support (p=0,03), and nurse’s support (p=0,001). Suggested to the nurses in pediatric surgery room to increase the information support like counseling face to face with the parents during the preoperative period, so that can increasing the knowledge of parents.